Gellan Gum Enhances the Quality of Egg-Based Yoghurt by Changing the Water Phase Distribution and Improving the Gel Texture - Yuanyuan Zhang; Jianwei Zang; Shutong Liu; Bingxu Yan; Daobang Tang; Jiguang Chen; Dongwen Li; Dayong Peng; Zebo Liu; Zhongping Yin (Foods)
Egg-based yoghurt (EBY) is a novel yoghurt fermented by lactic acid bacteria with high nutritional and health values, serving as a potential alternative to milk-based yoghurt. However, the hardness, adhesiveness, and water-holding capacity of egg-based yoghurt need to be further improved. In this study, the improvement in EBY quality by gellan gum and its underlying mechanism were investigated. The results showed that gellan gum significantly improved the quality of EBY (p < 0.05). Among the five concentration gradients tested, the EBY supplemented with 0.045% gellan gum exhibited the best quality with the highest sensory score of 83.57. With the increasing amount of gellan gum, hydrogen bonding interactions in the yoghurt significantly increased, while ionic bonding remained unchanged, but hydrophobic interactions and disulphide bonding gradually decreased. Low-field NMR assay results demonstrated that gellan gum significantly raised the amount of strongly bonded water while decreasing the amount of immobile water in the yoghurt. Confocal laser scanning microscopy revealed that EBY with 0.045% gellan gum had a better texture, whereas too much or too little gellan gum led to a coarser structure. In summary, gellan gum altered the water phase state and enhanced the water holding capacity through increased hydrogen bonding interactions, which consequently improved the yoghurt’s texture and sensory qualities. This study provides a reference for the development and application of EBY.